2017
DOI: 10.1089/jpm.2016.0059
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Physician Orders for Life-Sustaining Treatment Decisions: A Pilot Study

Abstract: Background: Physician Orders for Life-Sustaining Treatment (POLST) forms are used to document patient treatment preferences as medical orders. Prior research demonstrates that use of POLST alters medical treatments in a way that is consistent with the POLST orders. However, there are minimal data about the quality of POLST decisions, including whether they reflect the current preferences of well-informed patients. Objective: Evaluate the quality of POLST decisions. Design: Chart abstraction; interviews. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
0
30
0
4
Order By: Relevance
“…[11] A recent American study found discordance between Physician Orders for Life Sustaining Treatment forms and current treatment preferences. [15] The objective of this study was to explore the comprehension of ACP in people with cancer who have current advance care plans. how people with cancer comprehended advance care plans.…”
Section: Introductionmentioning
confidence: 99%
“…[11] A recent American study found discordance between Physician Orders for Life Sustaining Treatment forms and current treatment preferences. [15] The objective of this study was to explore the comprehension of ACP in people with cancer who have current advance care plans. how people with cancer comprehended advance care plans.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à procedência dos artigos: 45,8% foram desenvolvidos em países da América do Norte 13,14,16,18,20,22,24,26,29,33,34 , 41,7% em países da Europa 15,17,21,23,25,[30][31][32]35,36 , 8,3% em países da América do Sul 27,28 e 4,2% em um país da Oceania 19 . Os países que mais publicaram sobre esta temática foram os Estados Unidos 13,14,16,18,20,22,24,26,29,33 , seguido por Portugal 17,21,25,32 e Bélgica 23,30,31,35 .…”
Section: Resultsunclassified
“…Nove estudos integram essa categoria 13,14,16,18,19,24,29,33,34 e abordam as preferências atuais das pessoas idosas e a tomada de decisão em seus cuidados ao fim da vida considerando os princípios bioéticos.…”
Section: Categoria 2: Tomada De Decisão Nos Cuidados Ao Fim Da Vidaunclassified
“…To date however, no published studies have evaluated a decision aid for the entire POLST. Further, there is little research about the quality of POLST paradigm decisions, other than a small sample pilot study (Hickman et al, 2017) and a study evaluating an aid for section B of the West Virginia POST (Gallegos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the growing research investigating the completion of POLST paradigm forms, there is relatively little research investigating the quality of the decision-making process. Hickman et al (2017) conducted a small pilot study to investigate POLST paradigm decision quality. Participants were nursing home residents and surrogate decision-makers who had completed POLST paradigm forms in the past year.…”
Section: Limitations Of the Polstmentioning
confidence: 99%